Neonatal Outcomes of Large-for-Gestational Age Infants with or without Gestational Diabetes Mellitus - Begum, Taslima; Begum, Gulshan Ara; Chowdhury, Mahmood A; Ahmed, Wazir; Badrudddoza, Md (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2018)
Background: Infants are considered Large for Gestational Age (LGA)if their birth weight is greater than the 90th percentile for gestational age. Birth weight is influenced by a number of factors with maternal diabetes being one of the most common risk factor affecting birth weight. They have an increased risk for adverse perinatal outcomes. The aim of the present study was to compare the neonatal outcomes of LGA infants delivered by women with and without gestational diabetes mellitus. Methods: This is a prospective study of all live-born LGA infants of 37 weeks of gestation with a birth weight of 4000g admitted at Neonatal ward of Chattagram Maa Shishu-O-General Hospital (CMSOGH) between 1st August 2013 to 31st July 2014. Type of sampling was purposive convenient sampling. A total of 51 neonatal patients were included. Data was collected in case record form. Data collected for the mothers included age, parity, gestational age and mode of delivery. Data for the infants include sex, birth weight, birth length and laboratory test. Outcomes were compared between infants of diabetic mothers (Group A) and infants of non- diabetic mothers (Group B). Then data was analyzed by SPSS 17.0 program and presented by tabular method, diagram and chart. Results: Among fifty one study subjects, thirty were Infants of Diabetic Mothers (IDMs) while twenty one were non- IDMs. 19 (63.3%) of the IDMs were male while 11 (36.7%) were female. Among the 21 non-IDMs 10 (47.6%) were male and 11 (52.4%) were female. Male to female ratio was 1.4:1. 5 (16.7%) of the IDMs were delivered vaginally while 25 (83.3%) were delivered by Caesarian Section (CS) where as 8 (38.1%) of the non- IDMs were delivered vaginally while 13 (61.9%) were delivered by CS. Respiratory distress was the most common morbidity affecting 70% of the IDMs and 66.7% of the non-IDMs. TTN accounted for the majority of the respiratory distress cases, occurring in 17 of the IDMs and 12 of the non-IDMs. Regarding analysis of other clinical features, convulsion (63.3%) was present more in IDMs than in non-IDMs (52.4%) cyanosis was found more in IDMs (60%) than non-IDMs (38.1%). Hypoglycemia was found more in IDMs than in non-IDMs. Mean glucose values were 41.06±19.91mg/dl for IDMs and 53.06±28.96mg/dl for the non-IDMs (p=0.001). Hyperbilirubinemia was more frequently observed in IDMs than in non- IDMs. About 17 (56.6%) of the IDMs and 7(33.3%) of the non-IDMs developed jaundice during the period of hospital stay. Polycythemia was not observed in both the groups but PCV was higher in IDMs (53.96±6.36) compared to non-IDMs (50.50±8.76). Hypocalcemia was not peculiar to a specific group. Five of the IDMs had congenital anomaly, of which three of them had cardiac anomaly. One of the non-IDM was suffering from ventricular septal defect. Birth asphyxia was observed more in non-IDMs (71.4%) than in IDMs (53.3%).One of the IDMs and two of the non-IDMs sustained a brachial plexus injury following vaginal delivery. On an average, IDMs had a longer duration of hospital stay. Outcome was more fatal in IDMs. About six (20%) of IDMs died compared to two (9.5%) of the non-IDMs. That was found statistically significant (p=<0.05). Conclusion: LGA babies with diabetic mother had more adverse outcome in terms of mortality and blood glucose level. More concentration is needed to control blood glucose of mother during pregnancy. Also extra care for the babies is needed to avoid fatal neonatal outcomes. Chatt Maa Shi Hosp Med Coll J; Vol.16 (2); July 2017; Page 25-30